Actualización y aplicación de normas, procedimientos para la redacción de documentos administrativos en la Cooperativa de Ahorro y Crédito “Coopindigena” ltda - Pullotasig Pumashunta, Nelly Lucía (2015)
This research aimed to apply the updates standards, procedures in administrative drafting documents in order to improve the written communication and administrative management in the “Coopindigena” Ltda. Savings Credit Cooperative, it will implement a guide model and formats schemes of administrative documents to assist the institution in activities with excellent presentation and writing in the development administrative documents. This research was based on inductive - deductive methods studies - compilation and information synthesis from books and websites, also it relied on techniques such as a survey and an interview….